Identifying and Prioritizing Tourism Attractions in Ravansar Based on Tourist Attracting Potentials - Yousef Ghanbari; Hossein Komasi; Dawood Jamini; Azadََ Arianpour (جغرافیا و پایداری محیط)
Ravansar with diverse natural and human tourist attractions is one of the main tourist destinations of the western Iran and Kermanshah province which attracts many tourists annually. Due to the high tourism potential and diversity of attractions, prioritizing and identifying potential areas for tourism development in this region for specifying the strengths and weaknesses is very important and seems inevitable. This article from the viewpoint of its purpose is an applied one and according to its method is a descriptive - analytical study and survey. to achieve the goal of the article, 9 parameters including altitude , situation of infrastructure, number of tourists, facilities and services, accessibility, potentials of attraction surroundings, the ability to attract tourists in different seasons, economic impacts and the absence of natural hazards in seven most important tourist sites were selected and prioritized using TOPSIS techniques. For determining the weight of indices, views of 30 experts concerned with the tourism were analyzed using AHP method. The TOPSIS model results prioritized Ravansar tourist attraction sites as following: Ghori Ghaleh Cave with 0.766 score in first rank, Sarab Ravansar with 0.716 score in second rank, Kavat cave with 0.589 score in third rank, Oveys-e Gharani shrine, Sarab-e Javari, Tape Mousayi and Tagh-e Farhad with respectively 0.569, 0.65, 0.249 and 0.224 score were located in the next priorities. Finally, to enhance strengths and reduce obstacles and problems in seven different tourist attraction sites of Ravansar, some solutions were offered.